Multiyear temperature variation in tropical mountain peatlands from the southern Espinhaço Mountain Range in Brazil - Tassinari, Diego (2025)
Tropical mountain peatlands in Brazil’s Southern Espinhaço Range are vital ecosystems, acting as carbon reservoirs, hydrological buffers, and biodiversity hotspots while sustaining traditional livelihoods and preserving paleoenvironmental records. Despite their importance, peatlands outside protected areas face degradation by grazing and fires, threatening their ability to regulate ecosystem processes sensitive to temperature, such as greenhouse gas emissions, water cycling, biological activity, and organic matter decomposition. Since 2016, we have monitored peat temperatures in two contrasting peatlands–one preserved (within a protected area) and one disturbed (outside the protected area)–to understand how anthropogenic disturbances and climate variability impact these fragile ecosystems. Seasonal patterns dominated temperature variation, accounting for 60% of air and 81%–92% of peatland temperature variation. However, average temperatures and amplitudes differed between peatlands and depths. Interannual variability revealed stronger trends in the disturbed peatland, where a 1°C increase in air temperature caused the trend to increase 0.70°C–0.87°C on average at depths of 0.85 m–0.92 m. By contrast, the preserved peatland showed smaller increases (0.20°C–0.24°C) at comparable depths (1.06 m–1.24 m), suggesting a greater resilience. Temperature variation in the monitored peatlands was majorly driven by seasonal patterns, as revealed by time series decomposition and sinewave fit. Average temperature and amplitude varied between the two peatlands and among sampling sites, reflecting differences in environmental conditions and measurement depth. Interannual variability also exhibited distinct effects between peatlands and monitoring sites. The time series trend component showed more pronounced fluctuations at shallower depths and in the disturbed peatland. For every 1°C increase in the trend component of the air temperature, the trend component of the peatland time series increased by 0.70°C and 0.87°C on average at depths of 0.85 m and 0.92 m, respectively, in the disturbed peatland. In contrast, the preserved peatland exhibited smaller increases of 0.20°C and 0.24°C at comparable depths (1.06 m and 1.24 m). These findings highlight the potential for feedback responses between peatland disturbance and climate change, threatening their critical role in regulating carbon and water cycles. Expanding long-term monitoring, strengthening conservation efforts, and raising public awareness are essential to safeguard the ecosystem services provided by tropical mountain peatlands.